TRANSFORMING TAX ADMINISTRATION: FROM REPORTING AUTOMATION TO INTELLECTUAL CONTROL (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This research report analyzes the fundamental stages of the digital transformation of tax administration, in particular, the mechanisms of transition from traditional automation processes to intelligent control systems based on artificial intelligence. The focus of the research is on the tax reforms of the Republic of Uzbekistan for 2023–2025, in particular, the results of joint projects with the World Bank and the International Monetary Fund.